Dynamic behaviour of lactate values during mild hypothermia in patients with cardiac arrest. Issue 2 (June 2014) - Lazzeri, Chiara; Gensini, Gian Franco; Sori, Andrea; Bernardo, Pasquale; Chiostri, Marco; Tommasi, Eleonora; Grossi, Francesco; Valente, Serafina
Background and Methods: The present investigation was aimed at assessing the dynamic behaviour of lactate values during hypothermia in 33 patients with cardiac arrest. Results: Fifteen patients died during intensive care stay (15/33, 45.5%). When compared to survivors, they were older (survivors 50.7±14.7 vs. non-survivors 70.1±10.4 years, p <0.001) and exhibited a significantly higher APACHE score (survivors 21.9±3.9 vs. non-survivors 27.5±4.6, p <0.001). A higher incidence of non-shockable rhythms was observed in non-survivors ( p =0.026) who showed a longer collapse–recovery of spontaneous circulation time ( p =0.01). During hypothermia, lactate values showed a progressive and significant decrease despite no significant change in mean arterial pressure and central venous pressure (i.e. independently of blood pressure values and volaemia). Lactate values when measured during hypothermia were related to in-intensive cardiac care unit (in-ICCU) death. Conclusion: In our series, lactate values measured during hypothermia hold a prognostic role in these patients since they are related to in-ICCU death.